2009
DOI: 10.1158/0008-5472.can-08-1694
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of E-cadherin and PTEN Regulates Morphogenesis and Growth Arrest in Human Mammary Epithelial Cells

Abstract: Phosphatase and tensin homologue deleted on chromosome 10 (PTEN) is a dual-function phosphatase with tumor suppressor function compromised in a wide spectrum of cancers. Because tissue polarity and architecture are crucial modulators of normal and malignant behavior, we postulated that PTEN may play a role in maintenance of tissue integrity. We used two nonmalignant human mammary epithelial cell lines that form polarized, growth-arrested structures (acini) when cultured in three-dimensional laminin-rich extrac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 43 publications
(48 reference statements)
2
68
0
Order By: Relevance
“…In agreement, recent studies in breast cancer cells have implicated E-cadherin-mediated cell-cell adhesion in the regulation of PTEN. Specifically, exogenous expression of E-cadherin increases, whereas function-blocking E-cadherin antibody or siRNA-mediated knockdown reduces, PTEN protein levels Fournier et al, 2009). PTEN transcription is regulated by numerous transcription factors.…”
Section: Regulation Of Pten Levels By Cell Density and E-cadherin-cadmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement, recent studies in breast cancer cells have implicated E-cadherin-mediated cell-cell adhesion in the regulation of PTEN. Specifically, exogenous expression of E-cadherin increases, whereas function-blocking E-cadherin antibody or siRNA-mediated knockdown reduces, PTEN protein levels Fournier et al, 2009). PTEN transcription is regulated by numerous transcription factors.…”
Section: Regulation Of Pten Levels By Cell Density and E-cadherin-cadmentioning
confidence: 99%
“…It has been shown that PTEN transcription can be transactivated by early growth response gene 1 (Egr1), which binds directly to a consensus Egr1-binding motif in the PTEN promoter (Virolle et al, 2001). Recent studies suggest that E-cadherin modulates PTEN levels in breast cancer cells Fournier et al, 2009); however, the exact mechanism by which E-cadherin regulates PTEN levels is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…43 Further, the reduced expression of proteins such as Cadherins that mediate cell-cell contacts can correlate with tumor formation and progression, 44 conceivably through the loss of epithelial integrity and polarization. 45 Therefore, an augmentation of microwell platforms towards a mimickry of this cell-cell crosstalk ( Fig. 2A) would be of great benefit for many basic biological studies.…”
Section: Engineering Microwells As 2d Single Cell Microenvironmentsmentioning
confidence: 99%
“…We suggested that upexpression of HAPLN3 could contribute to the promotion of cell proliferation, migration, and angiogenesis by cooperation with versican or hyaluronan. Moreover, overexpression of CLDN16 dominated the alteration of cell polarity in breast cancer (9,18,31), and mutual up-expression of both CLDN16 and HAPLN3 could contribute to the development of breast cancer, although those mechanisms require further clarification.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…During cancer development, the destruction of tight junctions (8), as well as the deprivation of cell polarity (9,10) and increased cell mobility (11,12), contribute to cancer cell proliferation, invasion, and metastasis, and a poor prognosis. Claudin-16 (CLDN16), a member of the claudins family, is a tight junction protein and plays important roles in the maintenance of cell polarity, cellular arrangement, adhesion, paracellular transport, and ionic permeability of various epithelia (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%